2014
DOI: 10.1111/jfd.12229
|View full text |Cite
|
Sign up to set email alerts
|

Kaolinitic clay protects against Flavobacterium columnare infection in channel catfish Ictalurus punctatus (Rafinesque)

Abstract: Columnaris disease, caused by the bacterial pathogen Flavobacterium columnare, continues to be a major problem worldwide in both wild and cultured freshwater finfish. Despite the far-reaching negative impacts of columnaris disease, safe and efficacious preventatives and curatives for this disease remain limited. In this study, we evaluated the potential of kaolin (Al2 Si2 05 (OH)4 ), a type of clay, for the prevention of columnaris disease. Channel catfish, Ictalurus punctatus (Rafinesque), fingerlings were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…These findings are similar to those of Beck et al. (), who reported a two‐log reduction in the number of F. columnare cells present in the supernatant of kaolin‐treated in vitro cultures as compared to kaolin‐free cultures and found that the plating of settled bacterial–kaolin complexes on appropriate media revealed that bacteria remained viable. The reduced amount of bacteria in the upper phase but insignificant increase of bacterial cells at the sediment of the sample treated with 0.025% kaolin indicates that they are still in mid‐phase and may be unable to form large enough flocs to settle out.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are similar to those of Beck et al. (), who reported a two‐log reduction in the number of F. columnare cells present in the supernatant of kaolin‐treated in vitro cultures as compared to kaolin‐free cultures and found that the plating of settled bacterial–kaolin complexes on appropriate media revealed that bacteria remained viable. The reduced amount of bacteria in the upper phase but insignificant increase of bacterial cells at the sediment of the sample treated with 0.025% kaolin indicates that they are still in mid‐phase and may be unable to form large enough flocs to settle out.…”
Section: Discussionsupporting
confidence: 91%
“…In the kaolin‐treated tanks, kaolin (1 g/L) was slowly added to the water 5 min prior to the challenge and was mixed thoroughly as described previously (Beck et al. ). Subsequently, 100 mL of the bacterial culture were added (immediately after fin‐clipping) to each challenge tank, resulting in a final concentration of approximately 1.5 ± 0.1 × 10 7 CFU/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The water was provided through the ultra‐low‐flow water delivery system at a rate of 30 mL min −1 (Beck et al . ,b). LV‐359‐01 was inoculated in 1 L of FCGM and cultured until an OD signal of 0.80 at 550 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Fish were experimentally challenged with F. co lum nare isolate LSU-066-04 (genomovar II) obtained from Dr. J. Hawke (Louisiana State University), an isolate originating from an outbreak in largemouth bass which has previously been used to initiate columnaris disease in channel catfish Ictalurus punctatus in our challenge system (Beck et al 2014). The isolate was retrieved from storage at −80°C and streaked on Ordal's media (Anacker & Ordal 1959); after 48 h, the isolate was dislodged from the agar using a sterile cotton swab and inoculated into 5 ml of F. columnare growth medium (FCGM;Farmer 2004).…”
Section: Flavobacterium Columnare Challengementioning
confidence: 99%